A Are renewable energy and nonrenewable energy substitutes or complementary for economic growth and environment quality: an international evidence: an international evidence - Gmidène, Samia; Zaidi , Saida; Zouari Ghorbel , Sonia (International Journal of Accounting and Economics Studies, 2024)
The aim of this paper is to examine the interrelationships between renewable energy, nonrenewable energy consumption, CO2 emissions and economic growth. It considers substitution and complementarity between renewable and nonrenewable energies, by means of dynamic panel data models in simultaneous-equations for a global panel consisting of 107 countries. The time component of our dataset is 2000–2017 inclusive. To make the panel data analysis more homogenous, we also investigate this interrelationship for a number of sub-panels, which are constructed based on the income level of countries. In this way, we end up with three income panels; namely, high income, middle income, and low income panels. In the empirical part, we draw on the growth theory and augment the classical growth model, which consists of capital stock, labor force and inflation, with CO2 emissions and energy. Generally, we show mixed results about the interrelationship between renewable energy, non-renewable energy consumption, CO2 emissions and economic growth.